Supraclavicular area swelling in neurofibromatosis patient. Issue 5 (September 2018) - Lee, Duk Hee; Lee, Jae Hee; Kim, Keon; Lim, Ji Yeon; Choi, Yoon Hee
Neurofibromatosis 1 is an autosomal dominant disorder characterized by cafe-au-lait spots, cutaneous neurofibroma, and bony deformities. Vascular abnormality such as stenosis, aneurysm, or rupture associated with neurofibromatosis 1 is rare. Rupture of vertebral artery aneurysm into the thoracic cavity is extremely rare. The outcomes of patients with aneurysmal ruptures are very poor when spontaneous hemothorax occur. A 31-year-old woman presented to the emergency department with left shoulder pain and with both lower chest wall pain and left supraclavicular area swelling. The chest computed tomography scan revealed about 4-cm pseudo-aneurysm probable arising from the left vertebral artery with large hematoma at left supraclavicular area. Neurofibromatosis 1 is generally being regarded as a benign disease but has the potential for serious vascular complications. When aneurysms were ruptured, cervical hematoma, hemothorax, or hypotension was developed. It is potentially a life-threatening condition, so it must require emergent management. Emergency physicians must remember the relation of neurofibromatosis 1 and serious vascular complications and ensure rapid access to rule out vascular lesions, so as to prevent the life-threatening condition.